Evaluation of a solar/UV annular pilot scale reactor for 24 h continuous photocatalytic oxidation of n-decane - Ricardo A. R. Monteiro (2015)
A pilot scale single-pass continuous-flow annular photoreactor (r(annulus) = 21.3 mm) was designed and manufactured featuring a compound parabolic collector (CPC) to capture both direct and diffuse solar radiation and, simultaneously, artificial UVA lamps, in order to examine the possibility of working continuously day and night. Cheap, lightweight and easily shaped cellulose acetate materials, which are transparent in the TiO2 activation range, were used as supports, as an alternative to classic porous solid monolithic structures. Such configuration allows that only 1% of the reactor volume is filled with photoactive material. The photocatalytic oxidation (PCO) of n-decane (C-dec, (feed) = 10 ppm, Q(feed) = 2 L min(-1), tau = 44 s) over cellulose acetate monolithic structures coated with different TiO2-based photocatalytic films (L-catalytic (bed) = 144 cm) was studied under solar and artificial UVA radiation. Gas-phase n-decane conversions up to 100% were attained using P25 or PC500 photocatalytic films under solar irradiances starting from 16 W-uv m(-2) in the morning (sunrise, increasing temperature) and down to 3 W-uv m(-2) in the afternoon (sunset, decreasing temperature). An increase of the UV irradiance at total n-decane conversion promotes the formation of CO2. The excess of photons reaching the photocatalytic bed favours the direct reaction pathway of CO2 generation. The PCO of n-decane enhanced 29% resulting in 100% of conversion using PC500 film instead of P25 film, under artificial UVA radiation (I = 29W m(-2)). Results indicate that combining both radiation sources, a 24 h continuous PCO process towards the removal of n-decane can be accomplished.